System design choice in the sharing economy: How different institutional logics drive consumer perception and consumers' intention to use sharing systems - Valentin Clemens; Christopher Albert Sabel; Johann Nils Foege; Stephan Nüesch (Schmalenbach Journal of Business Research (SBUR), 2022)
The sharing economy provides consumers with temporary access to various products. As a~growing business trend that continuously attracts new consumers, it motivates businesses to rapidly develop new system designs. In this study, we investigate how the system design choices of sharing systems for products affect consumers' perceptions of the system and consequently their intention to use a~system. Building on institutional logics, we examine how the logics inherent in two system designs-the community logic in peer-to-peer (P2P) systems and the corporate logic in business-to-consumer (B2C) systems-affect consumer perceptions. We argue that consumers perceive P2P and B2C logics differently regarding logics' economic benefits, product scarcity, sustainability benefits, and social benefits. To test our theory, we conducted a~scenario experiment with 1259~participants from the UK. Our findings suggest that consumers perceive P2P systems as yielding higher economic, sustainability, and social benefits than B2C systems, and that these benefits increase consumers' intention to use the system. However, we also find that P2P systems suffer from the risk of product scarcity, reducing consumers' intention to use such systems. In summary, our findings show that system design affects consumers' perceptions and that different designs attract consumer groups with different preferences.
Keywords: 650; Business-to-consumer; Consumer perception; Institutional logics; Peer-to-peer; Sharing economy